2017
DOI: 10.1016/j.biortech.2017.05.132
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and optimization for plasma electrolytic liquefaction of sawdust

Abstract: In this work, plasma electrolytic technology was successfully employed to achieve fast liquefaction of sawdust when polyethylene glycol 200 (PEG 200) and glycerol were used as liquefacient in the presence of the catalyst sulfuric acid. Results showed that H ions could heat the solution effectively during the plasma electrolytic liquefaction (PEL) process. The influence of some key parameters including liquefaction time, catalyst percentage, liquefacient/sawdust mass ratio, and PEG 200/glycerol molar ratio on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…In the phase U3 (600-700 V), the electric field and the kinetic energy of the ions in the solution are significantly enhanced, resulting in an obvious increase in the solution temperature and the formation of an arc discharge near the cathode followed by the solution boiling. Eventually, the gaseous products are generated by the boiling surrounded the cathode, which causes the current drop sharply from 0.22 A to 0.13 A. Xi et al also reported the dependence of the current and applied voltage [43,44]. It showed that there were also the increasing and decreasing stage of the current on the studied voltage range but there was no constant current range.…”
Section: A Plasma Liquefaction Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the phase U3 (600-700 V), the electric field and the kinetic energy of the ions in the solution are significantly enhanced, resulting in an obvious increase in the solution temperature and the formation of an arc discharge near the cathode followed by the solution boiling. Eventually, the gaseous products are generated by the boiling surrounded the cathode, which causes the current drop sharply from 0.22 A to 0.13 A. Xi et al also reported the dependence of the current and applied voltage [43,44]. It showed that there were also the increasing and decreasing stage of the current on the studied voltage range but there was no constant current range.…”
Section: A Plasma Liquefaction Characteristicsmentioning
confidence: 99%
“…Similar conclusions are supported by Xi et.al, who performed the liquefaction of sawdust by using plasma method. They also indicated that the discharge phenomenon is much tender when using PEG 200 as the liquefacient alone compared with glycerin [44].…”
Section: Optimization Of Solvent Ratio On the Pcl Processmentioning
confidence: 99%
“…Overall, plasma electrolysis provides a new method for biomass liquefaction with low energy consumption. [186]…”
Section: Lignin Fractionation From Biomassmentioning
confidence: 99%
“…Thus, biomass fractionation was accomplished rapidly as compared with other liquefaction methods. Overall, plasma electrolysis provides a new method for biomass liquefaction with low energy consumption …”
Section: Lignin Fractionation By Electrochemical Processmentioning
confidence: 99%
“…Steinberg (2006) used plasma technology to convert fossil fuels and biomass into electricity, hydrogen, and liquid fuels. Recently, Xi et al (2017) and Jiang et al (2019) combined plasma electrolysis in the presence of sulfuric acid as the catalyst with traditional polyethylene glycol 200 (PEG 200) and glycerol co-solvent liquefaction to achieve fast liquefaction of biomass sawdust. The results show that the plasma electrolysis liquefaction process causes sawdust to decompose into small molecules in liquid and gas forms, which is directly related to the changes in solution resistance parameters in the plasma electrolysis liquefaction process.…”
Section: Introductionmentioning
confidence: 99%